An Unexpected Electrochemical Performance Enabled by In Situ Formed Quasi‐Metal‐Semiconductor Heterojunction with Innumerous P‐Type Anti‐Barrier Layer. Issue 14 (17th February 2023) - Li, Yu; Cai, Jinyan; Zhang, Jiawei; Chen, Zhen; Wang, Gongming; Chen, Qingguo; Chen, Minghua
Abstract: Nickel/cobalt‐based materials with diffusion‐controlled redox reactions have shown potential as the battery‐type electrode for battery‐supercapacitor hybrid devices. However, the sluggish redox kinetics and poor structural durability greatly restrict the rate capability and cycling lifespans of these materials to match up with activated carbon electrodes. Herein, an in situ split quasi‐metal‐semiconductor (CoO‐Ni3 N) heterostructure is constructed via a simple hydrothermal reaction, delivering a superior areal capacitance of ≈3800 mF cm −2 (≈sevenfold higher than bare CoO and Ni3 N) and top‐level cycling performances (32 000 cycles with ≈98% retention) among the battery‐type materials in supercapacitors. The P‐type anti‐barrier layer formed at the CoO‐Ni3 N heterostructure interface with a sufficiently large depletion width, effectively optimizes the electron structures and OH − adsorption abilities of building blocks. In situ Raman and various ex situ characterizations uncover that the CoO‐Ni3 N heterostructure undergoes different redox routes with enhanced reversibility and kinetics compared to building blocks, which are responsible for the improved capacitance and rate performance. Based on the designed electrode, the assembled device shows rare rate performance and cycling lifespans in the context of previous reports. The work unravels the role of heterojunctions in semiconductor theory and may extend to heterostructure design in other electrochemical energy storage fields. Abstract : The electronic structure and energy storage mechanism of the in situ split CoO‐Ni3 N heterostructure electrode are strongly affected by the quasi‐metal‐semiconductor heterojunction and innumerous interfaces, leading to enhanced charge/ion transport kinetics, redox kinetics, OH − adsorption ability, and structural durability. This work offers an in‐depth understanding of the superiorities of the in situ split heterostructure and may extend to other applications.